Dynamic Study of a Capacitive MEMS Switch with Double Clamped-Clamped Microbeams - Hatem Samaali; Fehmi Najar; Slim Choura (Shock and Vibration)
We study a capacitive MEMS switch composed of two clamped-clamped exible microbeams. We first develop a mathematical model for the MEMS switch where the upper microbeam represents the ground transmission line and the lower one represents the central transmission line. An electrostatic force is applied between the two microbeams to yield the switch to its ON and OFF states. We derive the equations of motion of the system and associated boundary conditions and solve the static and dynamic problems using the differential quadratic method. We show that using only nine grid points gives relatively accurate results when compared to those obtained using FEM. We also examine the transient behavior of the microswitch and obtain results indicating that subsequent reduction in actuation voltage, switching time, and power consumption are expected along with relatively good RF performances. ANSYS HFSS simulator is used in this paper to extract the RF characteristics of the microswitch. HFSS simulation results show that the insertion loss is as low as −0.31 dB and that the return loss is better than −12.41 dB at 10 GHz in the ON state. At the OFF state, the isolation is lower than −23 dB in the range of 10 to 50 GHz.